UNDERSTANDING FRESHMEN STUDENTS’ PERCEPTIONS OF BASIC ENGLISH SKILLS, LEARNING BARRIERS, AND STRATEGIES IN AN INDONESIAN UNIVERSITY - Ferawaty Syam; Annery Fienta; Muhammad Asrul Sultan; Hardianti (Institut Agama Islam Negeri Bone, 2025)
This study investigates freshmen students’ self-perceived basic English abilities in a non-English department at an Indonesian university. Using a descriptive quantitative survey design, data were collected from 101 participants through a six-item multiple-choice questionnaire administered via an online survey platform. The findings reveal that most students rate their overall English proficiency as poor and show low confidence in using English in daily contexts. Speaking and listening emerged as the most frequently identified weak skills, while grammar, vocabulary, fluency, and reading comprehension were cited as major challenges. Students’ experiences learning English in high school were mixed, with many reporting inadequate preparation for university-level demands. In terms of learning strategies, students primarily relied on self-study and reading, with fewer attending formal courses, and some reporting no deliberate strategy at all. These results suggest a gap between students’ secondary education experiences and their readiness for academic English tasks. The study highlights the need for universities to provide early support focusing on communicative competence, foundational language skills, and confidence-building activities. Limitations include the exclusive use of self-reported data, a limited number of survey items, and a single-site sample. Recommendations for future research include larger samples, mixed-methods approaches, longitudinal studies, and evaluations of targeted interventions to improve students’ basic English competence